Healthy emotions and relationships with teens—a guide for parents: An intervention development study of a parent-based intervention for adolescents with depression. (July 2022) - Reigstad, Kristina M; Gunlicks-Stoessel, Meredith L; Westervelt, Ana; Gearity, Anne R
Problems in parent-adolescent relationships are a significant risk factor for the development of depression in adolescents. This paper describes the development of a novel and innovative intervention for parents of depressed adolescents that targets attachment-related parenting behaviors, including parent responses to adolescents' emotions (Healthy Emotions and Relationships with Teens-A Guide for Parents [HEART-P];Reigstad, 2017 ) and provides results of an open pilot study that was conducted to assess the feasibility and acceptability of the intervention. 15 parents/parent dyads of adolescents (age 12–18) with a depression diagnosis (14 mothers, and one father) participated in a 10-week open trial of HEART-P. Data regarding acceptability and feasibility were collected. Self-report measures of parenting, stress, family relationships, and adolescent depression were also completed by parents at baseline, week 10, and 2 months post-intervention. Parents completed the intervention with 100% adherence to the protocol and expressed high levels of satisfaction. Parents reported reductions in parenting stress, improvement in the quality of their relationship with their adolescent, and improvement in the perception of their parenting skills, with effect sizes in the medium to large range. Adolescents reported reductions in depression, with effect sizes in the small to medium range. Outcomes appear positive and promising, and the intervention was feasible to implement and acceptable to families. Conducting a full-scale randomized control trial to evaluate the efficacy of this newly developed intervention is warranted and timely given the public health need for improved depression treatment outcomes.